Implementasi Program Tahfidz Dalam Meningkatkan Daya Ingat Hafalan Mahasantri Ma'had Al-Jami'ah Unhasy Tebuireng Jombang - Islaamiyyah , Rahmatun; Sa'diyah, Maidatus (PAI FAI UNHASY Tebuireng Jombang, 2026)
The tahfidz program has a very important contribution in improving students' memory. Memorizing the Qur'an, which is the core of this program, not only enriches religious knowledge but also has a positive impact on children's cognitive, emotional, and social abilities. This study aims to describe the implementation of the tahfidz program in improving the memorization memory of students at Ma'had Al-Jami'ah Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang and identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a case study type. The results show that the implementation of the tahfidz program at Ma'had Al-Jami'ah, which is carried out through daily muroja'ah, group halaqah, and periodic evaluations, contributes positively to improving students' memorization memory. Supporting factors include self-motivation, guidance from ustadz/ustadzah, a religious environment, and discipline in participating in activities. Inhibiting factors include limited time management, physical fatigue, and academic workload. Thus, optimizing planned and balanced religious activities with lecture activities can improve the quality of students' memorization.